2022
DOI: 10.1101/2022.04.28.489882
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-Specific Effects of Psychedelic Drug Exposure on Central Amygdala Reactivity and Behavioral Responding

Abstract: Psilocybin, and its active metabolite psilocin, have been shown to elicit rapid and long-lasting symptom improvements in a variety of affective psychiatric illnesses. However, the specific mechanisms behind these therapeutic effects remain relatively unknown. The central amygdala (CeA) is a primary output region within the extended amygdala that is heavily dysregulated in affective psychiatric disorders. Here, we utilized fiber photometry to measure changes in CeA reactivity to an aversive air puff stimulus af… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 80 publications
(253 reference statements)
0
3
0
Order By: Relevance
“…Here, we showed that psilocin administration produced increases in reactivity within the PVN in males, but no significant effects were seen in females, and no differences in either sex were seen at more prolonged time points. Interestingly, these effects are in contrast to previous findings from our group, wherein we found acute sex-specific effects of psilocin administration causing increased CeA reactivity in females only 30 . One potential mechanism for this could involve known inhibitory PVN→CeA circuitry, wherein oxytocinergic projections from the PVN to the CeA activate GABAergic cells in the lateral CeA (CeL) that then inhibit output neurons of the CeA located in the medial CeA (CeM) 43 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Here, we showed that psilocin administration produced increases in reactivity within the PVN in males, but no significant effects were seen in females, and no differences in either sex were seen at more prolonged time points. Interestingly, these effects are in contrast to previous findings from our group, wherein we found acute sex-specific effects of psilocin administration causing increased CeA reactivity in females only 30 . One potential mechanism for this could involve known inhibitory PVN→CeA circuitry, wherein oxytocinergic projections from the PVN to the CeA activate GABAergic cells in the lateral CeA (CeL) that then inhibit output neurons of the CeA located in the medial CeA (CeM) 43 .…”
Section: Discussioncontrasting
confidence: 99%
“…Given the observed persistent effects of psychedelics in clinical trials and previously published work 30 , we assessed PVN reactivity at multiple time points following injection. In males, acutely elevated PVN reactivity to the air puff following injection was restored at the 2-and 7-day follow-up time points.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that female animals were used exclusively in these studies and that psilocybin has been shown to have effects that differ based on biological sex in rats and mice in terms of behaviour 95 , regional brain reactivity 96 and structural neuroplasticity 46 . Future studies should aim to examine how psilocybin influences serotoninergic tone via other (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The key outcomes of this study underline the fact that animal studies are required for understanding the mechanisms that underlie the therapeutic efficacy of psilocybin because they allow detailed interrogation of behaviour and brain function in the absence of effects of expectancy. It is important to note that female animals were used exclusively in these studies and that psilocybin has been shown to have effects that differ based on biological sex in rats and mice in terms of behaviour 93 , regional brain reactivity 94 and structural neuroplasticity 46 . Future studies should aim to examine how psilocybin influences serotoninergic tone via other (i.e.…”
Section: Discussionmentioning
confidence: 99%